Long-term hydrological drought monitoring and trend analysis in Blue Nile River basin - Kassa Abera Tareke (Heliyon)
This research aims to monitor the hydrological drought trends within the geographical confines of Ethiopia, Sudan, and Egypt in the Blue Nile River Basin. Historical drought circumstances in the basin were analyzed through the utilization of the stream flow drought index (SDI). The long-term historical drought trend was investigated via the application of the Mann – Kendall Sen (MK) test. Streamflow data were collected at the border (GERD) (Ethiopia) and Khartoum and Dongola (Sudan) spanning the period from 1900 to 2001. Four distinct temporal scales were examined, including monthly (SDI1), seasonal (SDI3), bi-annual (SDI6), and annual (SDI12) frequency. Notably, SDI1, SDI3, and SDI6 exhibited a higher frequency of drought occurrences, whereas SDI12 demonstrated lower frequencies, accompanied by the longest duration of drought in all gauged stations. For the preceding 102-year period, two extreme drought events were identified across all stations: 1912/1913 and 1913/1914 in the Border and Dongola stations, and 1912/1913 and 1986/1987 in the Khartoum station. Moreover, the SDI12 results revealed that severe drought events manifested three, six, and four times, in the Border, Khartoum, and Dongola stations, respectively. Furthermore, an investigation of historical extreme and severe drought patterns led to the conclusion that extreme hydrological drought does not pose an imminent threat to downstream nations, including Egypt and Sudan. However, the trend analysis revealed that an increasing drought trend was observed in the Autumn season across all stations, while a positive trend characteristic of a wet condition was observed in the remaining seasons. Annual trend analysis did not show any statistically significant findings. Nevertheless, the study highlighted the imperative role of soil and water conservation measures in upstream countries, such as the Ethiopian highlands, in mitigating the prolonged effects of meteorological drought which gradually propagates into severe hydrological drought. Consequently, downstream nations must engage in cooperative efforts with upstream countries to address this issue collectively, rather than bestowing sole responsibility on the latter.